Adaptation and Psychometric Evaluation of the Santa Clara Brief Compassion Scale in Turkiye - Yavuzer Bayrak, Nisa; Bahcecioglu Turan, Gulcan; Cevik Akyil, Rahsan (Springer, 2026)
This study aimed to adapt the Santa Clara Brief Compassion Scale into Turkish and evaluate its psychometric properties, with the goal of providing a concise and culturally appropriate tool to assess compassion in healthcare and research contexts. This methodological study was conducted on 325 individuals aged 18 and over in Turkey between April and May 2025. Data were collected online using a demographic form and the Santa Clara Brief Compassion Scale. Content validity was evaluated by expert review. Construct validity was tested with confirmatory factor analysis, and reliability was assessed through Cronbach's alpha, McDonald's Omega, and test-retest analysis. Content validity indices indicated excellent agreement (I-CVI = 0.90-1.00; S-CVI = 0.99). Factor analysis indicated that the item loadings varied from 0.55 to 0.89. The fit indices were as follows: chi(2) = 5.67, SD = 3 (p < 0.05), chi(2)/SD = 1.89, RMSEA = 0.052, CFI = 0.99, SRMR = 0.017, TLI = 0.99, RMR = 0.039 and AIC = 29.67. Overall scale Cronbach's alpha coefficient was 0.805, and the Omega reliability coefficient was 0.801. As a result of the item analysis, it was determined that the item-total correlation coefficients for the items in the test varied between 0.494 and 0.697. The brief version maintained adequate validity while preserving the original item composition. The Turkish version of the Santa Clara Brief Compassion Scale demonstrated strong validity and reliability. This brief and culturally adapted tool can be applied to the general adult population and offers nursing and healthcare professionals, as well as researchers in social and behavioral sciences, a practical means to evaluate compassion. Its use may support evidence-based practice, guide interventions to foster compassionate care, and contribute to future research aimed at improving well-being and patient outcomes.
Keywords: Adaptation; Nursing; Santa Clara Brief Compassion; Scale; Psychometric evaluation